Effects of imidacloprid exposure on Chironomus riparius Meigen larvae: linking acetylcholinesterase activity to behaviour - Azevedo-Pereira, H. M. V. S.
Imidacloprid (IMI) is an insecticide that interferes with the transmission of stimuli in the nervous system of insects. It is neurotoxic by mimicking nicotine through its binding to the nicotinic acetylcholine receptor. In this work, experiments comprising 96 h exposure followed by 48 h in clean medium were conducted to evaluate the toxicity of IMI to Chironomus riparius and its potential recovery. Behavioural parameters and AChE activity were assessed. After 96 h exposure to IMI, AChE activity, and the behaviour parameters ventilation and locomotion were reduced. There were no signs of recovery after removal to clean water for 48 h. Ventilation behaviour was the most sensitive parameter and the one with the highest correlation to AChE activity. Despite the possibility that IMI might be having an indirect effect on AChE activity, the behavioural endpoint showed a higher sensitivity than the biochemical response itself. This work highlights the importance of linking parameters with ecological relevance at individual level (behavioural parameters) with biochemical responses, to unravel xenobiotics mode of action. (C) 2011 Elsevier Inc. All rights reserved.